2010
DOI: 10.1186/cc8587
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypernatremia on patients with severe traumatic brain injury

Abstract: IntroductionWe previously showed that erythropoietin (EPO) attenuates the morphological signs of spinal cord ischemia/reperfusion (I/R) injury in swine [1] without, however, improving neurological function. The clinical use of EPO has been cautioned most recently due to serious safety concerns arising from an increased mortality in acute stroke patients treated with EPO and simultaneously receiving systemic thrombolysis [2]. Carbamylated EPO (cEPO) is an EPO derivative without erythropoietic activity and devo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 0 publications
1
14
0
6
Order By: Relevance
“…32 Hypernatremia has itself been associated with elevated creatinine 33 and increased mortality 19,[34][35][36] in patients with brain injury. In 4,296 patients admitted to a neurocritical care unit (only 17% patients had a TBI), results of a retrospective cohort study showed that a Na level [ 160 mEqÁL -1 was independently associated with an increased ICU mortality (odds ratio [OR], 4.8; 95% CI, 2.4 to 9.6).…”
Section: Discussionmentioning
confidence: 99%
“…32 Hypernatremia has itself been associated with elevated creatinine 33 and increased mortality 19,[34][35][36] in patients with brain injury. In 4,296 patients admitted to a neurocritical care unit (only 17% patients had a TBI), results of a retrospective cohort study showed that a Na level [ 160 mEqÁL -1 was independently associated with an increased ICU mortality (odds ratio [OR], 4.8; 95% CI, 2.4 to 9.6).…”
Section: Discussionmentioning
confidence: 99%
“…10 Hypernatremia (≥ 150 mEq/L) is seen in 30%-40% of patients with TBI. 6,11,15,19 The etiology of hypernatremia may not be strictly defined in patients with TBI, and this condition may be due to hyperosmolar therapy; hypovolemia; insensible free water losses; or high sodium load in intravenous fluids, feeds, or medications. 20 Additionally, hypothalamic dysfunction not resulting in overt diabetes insipidus may contribute to hypernatremia after TBI.…”
Section: Fig 1 Kaplan-meier Curve Showing Survival Rates By Severitmentioning
confidence: 99%
“…Também em 2009, Maggiore et al (71) (71) Em 2010, Shehata et al (142) apresentaram hiponatremia e 20 (25%), hipernatremia (143) . A incidência das disnatremias entre os pacientes com lesões difusas foi maior do que entre aqueles que tiveram hematoma intracerebral (p = 0,022).…”
Section: Hipernatremiaunclassified
“…(20,23) Também por motivos de maior exposição a situações de risco (imprudência no trânsito, incluindo o consumo de bebidas alcoólicas antes da condução; trabalhos fora de casa; uso de drogas ilícitas e envolvimento em contextos de violência e agressões físicas, entre outros), a população jovem também é a mais prevalente em estudos clínicos e epidemiológicos sobre o TCE. (1,20,146) Na revisão brasileira conduzida por Magalhães et al (20) , (7,71,72,140,142,144) Um pouco mais da metade dos pacientes avaliados neste estudo foi procedente de trabalho, foram considerados todos os traumas e não apenas o TCE. (29) No nosso estudo, os acidentes de trânsito foram os principais causadores de TCE na população estudada, compreendendo 76,7% de todas as causas, similarmente ao visto em outros estudos brasileiros e de outras regiões do mundo.…”
Section: Coleta De Dadosunclassified
See 1 more Smart Citation